Use of intraoral three-dimensional images for the identification of dental morphological traits related to ancestry estimation - Santo, E (2021)
Victim identification through dental features is one of the main objectives of forensic dentistry. In circumstances where information regarding antemortem dental records is missing, reconstruction of a biological profile can be useful as a first step toward personal identification. This reconstructive method provides valuable information, namely regarding the individual's ancestry, through the detection and degree of expression of dental morphological traits, which may help to restrict the number of candidates for identification. Technological advances allowed the development of alternative methods for dental evaluation, that complement or substitute those already in use in clinical practice. Among these, intraoral three-dimensional (3D) images are increasingly used in dentistry, as they have a high level of accuracy and are easy to obtain and store. However, a fundamental question regarding forensic dentistry is whether they allow recognition and analysis of dental morphological traits in detail, namely those related to ancestry. In this study, we evaluated 20 teeth morphological features using intraoral 3D imaging from 77 individuals from Northern Portugal. Our results showed that it was possible to identify and classify a large part of the main morphological traits used in the estimation of ancestry. As these 3D images present sufficient morphological detail to be classified, we believe that future applications of this technique can be expected in forensic dentistry.